PENGARUH KONSENTRASI DAN INTERVAL WAKTU PEMBERIAN URINE KELINCI PADA HASIL TANAMAN KACANG TANAH (Arachis hypogaea L. var. tala 1) - Fristiana Anggiastuti Dewi; Gembong Haryono; Nurul Anindyawati; Esna Dilli Novianto (Partner, 2023)
The application of rabbit urine on peanut plants has never been investigated. This research aimed to study the interaction of concentration and interval time of rabbit urine application towards peanut plants’ yield (Arachis hypogaea L. var. tala 1). This research was carried out using RCBD with two factors and three replications. The first factor is the concentration of rabbit urine 0, 20, and 40 ml/l respectively; while the second factor is the interval time of application, namely once every 4, 7, and 10 days. Results showed that both factors did not give significant effect for all observed parameters. Rabbit urine concentration was very low and did not fulfill the nutrient needs until they did not have any effect on the yield of peanut plants. In general, the treatments in this research did not have a significant effect on the yield of peanut plants.Key Words: peanut, Arachis hypogaea L. var. tala 1, rabbit urine